2017
DOI: 10.1002/pc.24690
|View full text |Cite
|
Sign up to set email alerts
|

In situ fabrication of cellulose nanocrystal‐silica hybrids and its application in UHMWPE: Rheological, thermal, and wear resistance properties

Abstract: Novel cellulose nanocrystal (CNC)‐silica (SiO2) nanohybrids with a better thermal stability were successfully fabricated by sol–gel method. In this unique hybrid architecture, it was found that silica particles were uniformly adsorbed/anchored by the CNC via covalent bonding and hydrogen bonding. Subsequently, the nanocomposites containing nanofillers (CNC‐SiO2 nanohybrids or CNC), ultrahigh molecular weight polyethylene (UHMWPE), polyethylene glycol (PEG), were prepared by the twin screw extrusion and their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Therefore, relying on some interaction mechanism, the inorganic phase with excellent thermal stability has a certain barrier effect on the thermal decomposition of the organic phase in the organic–inorganic hybrid. [ 30,31 ] In our previous work, [ 32,33 ] CNC‐polyhedral oligomeric silsesquioxane and CNC–SiO 2 nanohybrids with good thermal stability were successfully prepared. Hu et al [ 34 ] demonstrated that a hybrid filler of halloysite nanotubes (HNTs)/silica hybrid filler (HNTs‐silica) was fabricated by electrostatic self‐assembly in deionized water.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, relying on some interaction mechanism, the inorganic phase with excellent thermal stability has a certain barrier effect on the thermal decomposition of the organic phase in the organic–inorganic hybrid. [ 30,31 ] In our previous work, [ 32,33 ] CNC‐polyhedral oligomeric silsesquioxane and CNC–SiO 2 nanohybrids with good thermal stability were successfully prepared. Hu et al [ 34 ] demonstrated that a hybrid filler of halloysite nanotubes (HNTs)/silica hybrid filler (HNTs‐silica) was fabricated by electrostatic self‐assembly in deionized water.…”
Section: Introductionmentioning
confidence: 99%
“…According to Zhou et al [ 17 ], the presence of a filler in the UHMWPE matrix may contribute to some load-bearing capacity, such as increased stiffness and hardness, thus reducing the stress applied on the polymer. Studies by Li et al [ 18 ] and Wang et al [ 19 ] showed relatively lower wear volume, which was generated by the incorporation of cellulose nanocrystals (CNC), indicating the potential of nanocellulose materials as a UHMWPE filler for improving the wear resistance. The viability of MC3T3-E1 preosteoblast cells was significantly higher, while the inflammatory response of macrophage RAW 264.7 cells was lower when grown on UHMWPE/CNC composite, proving the biocompatibility and non-toxicity of nanocellulose materials as a UHMWPE filler.…”
Section: Introductionmentioning
confidence: 99%
“…The nanohybrid material prepared by hybridizing inorganic materials with CNCs not only can improve the thermal stability of the CNCs but can also exhibit unique properties by combining the properties of the original components. At present, some breakthroughs have been made in the research on CNC nanohybrid materials, and the inorganic materials used are related to graphene oxide, quantum dots, calcium carbonate, silica (SiO 2 ) etc. Among them, nano‐silica (nano‐SiO 2 ) has a small size effect, a large specific surface area and a quantum size effect, imparting high strength and thermal stability .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, nano‐silica (nano‐SiO 2 ) has a small size effect, a large specific surface area and a quantum size effect, imparting high strength and thermal stability . The novel CNC‐SiO 2 nanohybrid materials have been proved by our group to have excellent properties and have achieved satisfactory results in terms of the wear resistance of ultrahigh molecular weight polyethylene . Unfortunately, research on the use of novel organic–inorganic nanohybrid materials with excellent properties to improve the performance of FDM filaments and printed products has not been reported.…”
Section: Introductionmentioning
confidence: 99%